2021
DOI: 10.3390/sym13050750
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint Classification Based on Deep Learning Approaches: Experimental Findings and Comparisons

Abstract: Biometric classification plays a key role in fingerprint characterization, especially in the identification process. In fact, reducing the number of comparisons in biometric recognition systems is essential when dealing with large-scale databases. The classification of fingerprints aims to achieve this target by splitting fingerprints into different categories. The general approach of fingerprint classification requires pre-processing techniques that are usually computationally expensive. Deep Learning is emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…ey used probability calculations to identify the subblocks of the input image. More recently neural network fingerprint classification method is [16] where the proposed method is retrained over AlexNet, GoogleNet, and ResNet with an average precision of 95.55%, 92.51, and 94, 88 respectively. Matching fingerprints is the mechanism by which the similarity scores between the two fingerprints match.…”
Section: Related Workmentioning
confidence: 99%
“…ey used probability calculations to identify the subblocks of the input image. More recently neural network fingerprint classification method is [16] where the proposed method is retrained over AlexNet, GoogleNet, and ResNet with an average precision of 95.55%, 92.51, and 94, 88 respectively. Matching fingerprints is the mechanism by which the similarity scores between the two fingerprints match.…”
Section: Related Workmentioning
confidence: 99%
“…Do and his colleagues [19] proposed to fine-tune recent pre-trained deep learning models such as VGG16, VGG19 [52], ResNet50 [26], Inception-v3 [56], and Xception [10] for classifying fingerprint images. Militello et al [42] showed the performance of pre-trained CNNs, including AlexNet [31], GoogLeNet [55], and ResNet [26] for the fingerprint image classification. DeepPrint network [21] learns alignment and minutiae from fingerprint images, making fixed-length fingerprint representations of only 200 bytes.…”
Section: Related Workmentioning
confidence: 99%
“…The main reason for this success is the great diversity of the market and needs. New tasks such as medical imaging, Industry, Object Recognition [ 4 ], Autonomous Vehicle Navigation [ 5 ], Face Detection [ 6 ], Fingerprint Recognition [ 7 ], Fast Image Processing [ 8 ], and Robotic Navigation [ 9 ] have been tested at high accuracy. Furthermore, integrating artificial intelligence in image recognition is the subject of many uses.…”
Section: Introductionmentioning
confidence: 99%